Inhomogeneities in Network Structure and Excitability Govern Initiation and Propagation of Spontaneous Burst Activity - Okujeni, Samora; Egert, Ulrich (Frontiers in Neuroscience, 2019)
The mesoscale architecture of neuronal networks strongly influences the initiation of spontaneous activity and its pathways of propagation. Spontaneous activity has been studied extensively in networks of cultured cortical neurons that generate complex yet reproducible patterns of synchronous bursting events that resemble the activity dynamics in developing neuronal networks in vivo. Synchronous bursts are mostly thought to be triggered at burst initiation sites due to build-up of noise or by highly active neurons, or to reflect reverberating activity that circulates within larger networks, although neither of these has been observed directly. Inferring such collective dynamics in neuronal populations from electrophysiological recordings crucially depends on the spatial resolution and sampling ratio relative to the size of the networks assessed. Using large-scale microelectrode arrays with 1024 electrodes at 0.3 mm pitch that covered the full extent of in vitro networks on about 1 cm2, we investigated where bursts of spontaneous activity arise and how their propagation patterns relate to the regions of origin, the network’s structure, and to the overall distribution of activity. A set of alternating burst initiation zones dominated the initiation of distinct bursting events and triggered specific propagation patterns. Moreover, burst initiation zones were typically located in areas with moderate activity levels, i.e. at transitions between hot and cold spots. The activity-dependent alternation between these zones suggests that the local networks forming the dominating burst initiation zones enter a transient depressed state after several cycles (similar to Eytan et al 2003), allowing other burst initiation zones to take over temporarily. We propose that inhomogeneities in the network structure define such burst initiation zones and that the depletion of local synaptic resources limit repetitive burst initiation.